Characterization of Pregnant Women treated at the Center for Assisted Reproduction - Linett León Díaz; Aimé María Reyes Pérez; Práxedes Rojas Quintana; Aida María Reyes Pérez; Neysi Matilde Chávez González (Medisur)
Background: infertility is a health problem that does not cause death, disability or physical pain. However, it represents a crisis for couples whose life projects are threatened, suffering not only at the time of diagnosis and during treatment, but also in many everyday situations. Objective: to characterize patients diagnosed with infertility who achieved pregnancy after receiving treatment. Methods: a descriptive study of 384 infertile women who achieved pregnancy after being treated at the Territorial Center for Assisted Reproduction in Cienfuegos was conducted from January 2011 to December 2013. The variables analyzed included: age, age at first sexual intercourse, weight assessment, type and cause of infertility, medical management and pregnancy course. Results: most pregnant women were 26 to 30 years old. First sexual intercourse frequently occurred during adolescence. The most common cause of infertility was ovarian problems. Secondary infertility prevailed over primary infertility. There was an association between weight and pregnancy course, with an increased number of abortions among overweight and obese patients. Seventy six point nine percent of the patients who achieved pregnancy had a normal course of pregnancy. Conclusions: the characterization of these patients provides valuable information that can help to improve the quality of both municipal and provincial consultations.